Реализация формализованного перехода от алгоритма к программе средствами расширенной алгебры алгоритмов - Акуловский, В.Г. (Інститут програмних систем НАН України, 2008)
On an example of the opportunity of the formalized transition from algorithm to the program showed due to development and use of means of the expanded system of algorithmic algebras. There are showed the opportunities of transformation of the received program and auto-matic transition to the required programming lan-guage.